Classification Of the Problems of The Formation of Contemporary Spiritual Image of The Youth - Karimova Dilfuza Abduqayumovna (Zien Journals, 2022)
The social aspects of the formation of the modern spiritual image of young people, based on the ideas of legal consciousness, culture, spirituality, ideology, politics, public administration, behavior, law, ethics and social relations, are uniquely reflected in the creative heritage of the Eastern and Western traditions. The need to educate and bring up the younger generation is based on the conceptual ideas that serve the spiritual revival of society.
Keywords: Youth; spirituality; culture; activity